Statin use is associated with the reduction in hepatocellular carcinoma recurrence after liver surgery - Khajeh, Elias; Dooghaie Moghadam, Arash; Eslami, Pegah; Ali-Hasan-Al-Saegh, Sadeq; Ramouz, Ali; Shafiei, Saeed; Ghamarnejad, Omid; Abbasi Dezfouli, Sepehr; Rupp, Christian; Springfeld, Christoph; Carvalho, Carlos; Probst, Pascal; et al. (BMC cancer, 2022)
Hepatocellular carcinoma (HCC) is the sixth most common form of cancer worldwide. Although surgical treatments have an acceptable cure rate, tumor recurrence is still a challenging issue. In this meta-analysis, we investigated whether statins prevent HCC recurrence following liver surgery.
Gesehen am 11.08.2022